An Analysis of Sentences Error in Business Email Writing of Thai EFL Students - Sutakote, Chayakorn; Sarntong, Khomsin; Pawabutra, Pongsatorn (Journal of Education Studies, Chulalongkorn University, 2025)
This research aimed to 1) examine and classify types of sentence errors in business email writing produced by students, and 2) analyze the frequency, ranking, and percentage distribution of sentence errors identified in business email writing of students. The study analyzed 192 business emails with content focusing on inquiries, requests for action, information exchange, and scheduling/confirming appointments. The research instruments employed were 1) a collection form for email writing samples from students and 2) an assessment form for error classification. Data analysis used an adapted framework from Corder (1974) and Gass et al. (2013), implementing a systematic four-stage process including preserving original data, identifying errors by two researchers, categorizing errors using a framework synthesized from Dulay et al. (1982) and Langan (2012), and conducting quantitative analysis to determine frequency and percentage distribution. The findings revealed that: 1) four principal categories of sentence errors: independent clause structure, dependent clause structure, interrogative structure, and imperative structure, along with supplementary categories including run-on sentences and sentence fragments; 2) quantitative analysis revealed that omission errors were most prevalent (48.64%), followed by miscellaneous structural errors (23.78%), addition errors (22.70%), and word order errors (4.86%). These findings demonstrate the specific grammatical challenges encountered by Thai learners in professional communication contexts and contribute to understanding Thai EFL learners' interlanguage development in professional communication contexts. The study offers empirical evidence for enhancing business English curricula through targeted error remediation strategies.